OWNERSHIP STRUCTURE & RISK IN INDIAN BANKS: A COMPARISON OF PRIVATE AND PUBLIC BANKS (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Banking sector is one of dominant sector and represents growth and development of the economy. The sector has been one of the top performers in stock market. Indian Stock Market experienced great volatility during the period of 2007-2008. The study is about the ownership structure and risk in Indian banks which they encountered during the period of slow down in India. This paper examines the effect of ownership on performance and risk of commercial banks in India during the period 2000-2009. The study would examine whether there exists any significant difference in the performance and risk among Public and sector banks and effort has been made to evaluate the performance of bank before and after the period of 2007-2008 to evaluate and understand the ground reality in Indian banking sector. The study investigated that whether any significant difference exists in the performance and risk of ownership groups of private & public banks in India. Regression results would be used to examine the association between the size of the banks and non-performing loans, and between demand deposits & risky loans.